Avaliação do estresse de movimento em Jogos reabilitadores com realidade virtual imersiva no tratamento de torcicolo espasmódico - Farias, Douglas Lopes (2022)
In recent years, several scientists have investigated the use of Virtual Reality (VR) to support rehabilitation therapies, improving motor control, motivation, and, in some cases, providing analgesic effects, by distracting from pain. However, few are concerned with investigating the ergonomic effects of using this technology on the patient. This feature is the motivator for this study. The studies focus on the treatment of spasmodic torticollis, a very common disease in the area of information technology reported by users of information systems and computer programmers. There are some advantages in the use of ergonomic tests in VR that influence usability such as the playful potential of the exercises. However, there are some disadvantages that these tests clarify, such as: loss of immersion, discomfort and careless use. This work reports the application of ergonomic tests in a controlled scenario with non-injured patients, in which situations that can affect the effectiveness of the treatment were observed. Such situations include: assessment of the participants' biotype according to their Body Mass Index, Body Fat, Visceral Fat, Muscle Mass and Age. From this study, the impact of the weight of the device on the conduction of the exercise was investigated in order to identify the appropriate moment to end the interaction. To carry out the research, test groups were established with artifacts of different weights and different ages, which performed treatment movements through a game, and during the execution they answered a questionnaire through a "Think Aloud" protocol. A linear regression statistical method was used to analyze and validate the data and Principal Component Analysis (PCA) to identify the clusters of elements. It is concluded that the mentioned variables did not obtain dependence for interference at the appropriate time to end the exercise interaction. However, the data indicate that usability scenarios that consider the speed of movement interfere in the process.